2022
DOI: 10.1111/1467-8268.12652
|View full text |Cite
|
Sign up to set email alerts
|

Post‐COVID‐19 recovery for African economies: Lessons for digital financial inclusion from Kenya and Uganda

Abstract: As coronavirus disease-2019 (COVID-19) and other restrictions intensified, individuals, businesses and governments turned to mobile digital platforms to reduce the financial costs and mitigate the risk of spreading the virus within the population. Drawing on lessons from Kenya and Uganda, our study examines the drivers of digital financial inclusion as a pathway for financing post-COVID-19 recovery. We find that digital financial inclusion is higher in middle-aged male digital users with more SIM cards registe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 42 publications
(54 reference statements)
1
10
0
Order By: Relevance
“…Some firms advertised through and shifted to operations online, increasing sales and changing the mode of services. Mugume and Bulime [7] and Mburu [18] reached similar conclusions on sales during the lockdowns. Mburu [18] found that the lockdown in Kenya was associated with a 35 percent growth in online purchases of food, an 18 percent growth in pharmaceuticals, and a 54 percent growth in agribusinesses.…”
Section: Businesses Increased Online Presence During the Pandemicsupporting
confidence: 56%
“…Some firms advertised through and shifted to operations online, increasing sales and changing the mode of services. Mugume and Bulime [7] and Mburu [18] reached similar conclusions on sales during the lockdowns. Mburu [18] found that the lockdown in Kenya was associated with a 35 percent growth in online purchases of food, an 18 percent growth in pharmaceuticals, and a 54 percent growth in agribusinesses.…”
Section: Businesses Increased Online Presence During the Pandemicsupporting
confidence: 56%
“…Jain K. and Chowdhary R. [37] found that for surveyed respondents in India, performance expectancy and facilitating conditions were the determining factors that influenced the intention of individuals to use digital payment systems. Mugume R. and Bulime E. W. N. [38] found that in Kenya and Uganda, digital financial inclusion was higher in middle-aged male digital users with more SIM cards registered in their names. In African countries where financial inclusion is provided through mobile money accounts, such results clearly demonstrated the existence of gender and age gaps in access to digital financial services.…”
Section: Covid-19 Impacts On Households and Consumer Behaviormentioning
confidence: 99%
“…However, the final result depends on the share of consumers who will use a digital financial service; that is, on digital financial inclusion. Accordingly, one of the tasks of regulators is to promote digital financial inclusion by increasing trust and digital and financial literacy as well as ensuring the protection of consumer rights [38,68,69]. The analysis of existing programs for increasing digital financial inclusion and the development of recommendations for their implementation while taking into account the features of post-pandemic development will be the subjects of further scientific research.…”
Section: Covid-19 Impacts On the Financial System And Regulationmentioning
confidence: 99%
“…Therefore, increasing mobile money usage should be accompanied by increased consumer protection (OECD, 2018). Islam et al (2022); Mugume & Bulime (2022);Shaikh et al (2022) explain that although mobile money has various advantages, it also creates some problems. Those who do not have sufficient knowledge of using this service will be trapped at the risk of data privacy and fraud.…”
Section: The Effect Of Mobile Money Usage On Financial Inclusionmentioning
confidence: 99%